Internalisasi Nilai-Nilai Keislaman Dalam Konsep Baiti Jannati Keluarga Asatidzah - Abdullah, Muh. Rujib (Jurnal Keislaman, 2025)
This research discusses the concept of "Baiti Jannati" or "My Home is My Paradise" as an ideal in forming a harmonious family (usrah sakinah) among the asatidzah (Islamic teachers) of Sekolah Tinggi Dirasat Islamiyah. Emphasizing Islamic values and the teachings of the Qur'an and Hadith, this paper analyzes the importance of the roles of husbands and wives in creating a harmonious and happy household. Using a qualitative method involving interviews with 11 asatidzah, this study identifies key elements required to achieve family harmony and the faktors that may hinder the implementation of this concept. The results indicate that the application of religious values and effective communication between spouses are vital aspects in creating an ideal family. Enhancing moral education within the family environment is also recommended to strengthen the foundation of the "Baiti Jannati" concept in daily practice.